2019
DOI: 10.1007/s13770-019-00202-1
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Biodistribution of Human Bone Marrow-Derived Mesenchymal Stromal Cells Injected Intrathecally in Non-Obese Diabetic Severe Combined Immunodeficiency Mice: Preclinical Study

Abstract: BACKGROUND: Mesenchymal stromal cells (MSCs) have potent immunomodulatory and neuroprotective properties, and have been tested in neurodegenerative diseases resulting in meaningful clinical improvements. Regulatory guidelines specify the need to perform preclinical studies prior any clinical trial, including biodistribution assays and tumourigenesis exclusion. We conducted a preclinical study of human bone marrow MSCs (hBM-MSCs) injected by intrathecal route in Non-Obese Diabetic Severe Combined Immunodeficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
5
0
2
Order By: Relevance
“…In contrast, Kim et al [84] demonstrated that MSC migration from the spine to the brain is possible in a dose-dependent manner. Quesada et al [85] also demonstrated brain migration after intrathecal injection; (b) Intracerebral injection of MSCs: Wang et al [86] demonstrated that intracerebrally injected MSCs loaded with paclitaxel are capable of spreading from one cerebral hemisphere to another in a glioma model in mice in two days. These cells were found to spread from the healthy hemisphere to the glioma hemisphere and to invade the tumor.…”
Section: Injection Of Mscs Into the Central Nervous Systemmentioning
confidence: 99%
“…In contrast, Kim et al [84] demonstrated that MSC migration from the spine to the brain is possible in a dose-dependent manner. Quesada et al [85] also demonstrated brain migration after intrathecal injection; (b) Intracerebral injection of MSCs: Wang et al [86] demonstrated that intracerebrally injected MSCs loaded with paclitaxel are capable of spreading from one cerebral hemisphere to another in a glioma model in mice in two days. These cells were found to spread from the healthy hemisphere to the glioma hemisphere and to invade the tumor.…”
Section: Injection Of Mscs Into the Central Nervous Systemmentioning
confidence: 99%
“…One of the challenges is tracking the distribution of MSCs that are infused systemically. In vivo fluorescent imaging and/or quantification of human gene expression in various organs [ 42 , 43 ] should be performed in preclinical level for securing safety of MSC therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 130 ] In another study, 24 h after injection, the genetic material of MSCs was detected in the spinal cord and heart of mice and hearts and brains of animals four months later. [ 205 ] Both singular and repeated intrathecal injections of MSCs are currently being used in many clinical trials. [ 140,142,206 ] Some patients complain of backache; however, the biggest problem connected with intrathecal cell delivery is the risk of abnormal cerebrospinal fluid flow, caused by cell‐induced obstruction, which can result in hydrocephalus.…”
Section: Methods Of Transplantation Used In the Treatment Of Cns Damamentioning
confidence: 99%